EFEKTIVITAS SISTEM SELEKSI PAMONG KALURAHAN DALAM MEWUJUDKAN TATA KELOLA PEMERINTAHAN YANG PROFESIONAL (STUDI DI KALURAHAN CATURTUNGGAL KABUPATEN SLEMAN) - Andi Suwarno; Sri Widayanti (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
ABSTRACT Village officials (pamong kalurahan) play a strategic role in supporting local governance, public service delivery, and community development. Therefore, the recruitment and selection process must be conducted professionally in accordance with the principles of good governance to ensure the appointment of competent and high-integrity officials. This study aims to analyze the implementation of the pamong kalurahan selection system based on Sleman Regency Regional Regulation Number 10 of 2019 and its contribution to strengthening professional local governance in Caturtunggal Village, Depok Subdistrict, Sleman Regency. A qualitative approach employing a case study strategy was adopted. Data were collected through observation, semi-structured interviews with village government officials, the Village Consultative Body, the selection committee, and community representatives, as well as document analysis. The data were analyzed using data reduction, data display, conclusion drawing, and thematic analysis, while the credibility of the findings was ensured through source, method, and document triangulation. The findings indicate that the implementation of the selection system has been carried out in accordance with the established regulatory procedures and has been supported by effective stakeholder coordination, transparent information dissemination, and adequate supervisory mechanisms. A competency-based selection system has contributed to enhancing transparency, accountability, public participation, and the professionalism of village officials, although several challenges remain, including differences in public understanding of the selection mechanism and the social dynamics within the village. These findings demonstrate that a selection system consistently implemented in line with the principles of good governance serves as a strategic instrument for strengthening the quality of village governance. ABSTRAK Pamong kalurahan memiliki peran penting dalam mendukung penyelenggaraan pemerintahan, pelayanan publik, dan pembangunan di tingkat lokal sehingga proses seleksinya perlu dilaksanakan secara profesional berdasarkan prinsip good governance. Penelitian ini bertujuan menganalisis implementasi sistem seleksi pamong kalurahan berdasarkan Peraturan Daerah Kabupaten Sleman Nomor 10 Tahun 2019 serta implikasinya terhadap penguatan tata kelola pemerintahan yang profesional di Kalurahan Caturtunggal, Kapanewon Depok, Kabupaten Sleman. Penelitian menggunakan pendekatan kualitatif dengan strategi studi kasus. Data diperoleh melalui observasi, wawancara semi-structured dengan pemerintah kalurahan, Badan Permusyawaratan Kalurahan, panitia seleksi, dan unsur masyarakat, serta telaah dokumen yang berkaitan dengan pelaksanaan seleksi. Analisis data dilakukan melalui reduksi data, penyajian data, penarikan kesimpulan, dan analisis tematik dengan pengujian keabsahan menggunakan triangulasi sumber, metode, dan dokumen. Hasil penelitian menunjukkan bahwa implementasi sistem seleksi telah dilaksanakan sesuai tahapan yang diatur dalam regulasi dan didukung oleh koordinasi antarpemangku kepentingan, keterbukaan informasi, serta mekanisme pengawasan yang memadai. Penerapan sistem seleksi berbasis kompetensi berkontribusi terhadap peningkatan transparansi, akuntabilitas, partisipasi masyarakat, dan profesionalisme aparatur, meskipun masih dijumpai tantangan berupa perbedaan pemahaman masyarakat terhadap mekanisme seleksi dan dinamika sosial di lingkungan kalurahan. Temuan ini menegaskan bahwa implementasi sistem seleksi yang konsisten dengan prinsip good governance menjadi faktor penting dalam memperkuat kualitas tata kelola pemerintahan kalurahan.